Combination of clopidogrel and everolimus dramatically reduced the development of transplant arteriosclerosis in murine aortic allografts - Eckl, Sebastian; Heim, Christian; Abele-Ohl, Silke; Hoffmann, Julia; Ramsperger-Gleixner, Martina; Weyand, Michael; Ensminger, Stephan M. (Transplant International, 2010)
Summary Our group has shown that platelet inhibition with clopidogrel, an antagonist of the P2Y12 adenosine diphosphate receptor on platelets, reduced the formation of transplant arteriosclerosis. The aim of this study was to investigate whether a combination of cyclosporin or everolimus with clopidogrel has a beneficial effect on the development of transplant arteriosclerosis. Fully MHC mismatched C57Bl/6 (H2b) donor aortas were transplanted into CBA.J (H2k) recipients and mice received either clopidogrel alone (1 mg/kg/day) or in combination with cyclosporin (2 mg/kg/day) or everolimus (0.05 mg/kg/day). Grafts were analysed by histology and morphometry on day 30 after transplantation. In mice treated with clopidogrel alone, transplant arteriosclerosis was significantly reduced [intima proliferation 56 ± 11% vs. 81 ± 7% (control)/n = 7]. Daily application of everolimus reduced the development of transplant arteriosclerosis compared with untreated controls [intima proliferation of 29 ± 9% vs. 81 ± 7% (control)/n = 7]. Strikingly, combination of clopidogrel and everolimus almost abolished the formation of transplant arteriosclerosis [intima proliferation: 11 ± 8% vs. 81 ± 7% (control)/n = 7]. By contrast, combination of cyclosporin and clopidogrel compared with clopidogrel alone showed no additive effect. These results demonstrate that combination of platelet- and mammalian target of Rapamycin-inhibition can dramatically reduce the development of transplant arteriosclerosis. © 2010 The Authors.
CRIS-Team Scopus Importer:2024-06-04
Keywords: clopidogrel; mammalian target of rapamycin inhibitor; platelets; transplant arteriosclerosis

Delayed therapy with clopidogrel and everolimus prevents progression of transplant arteriosclerosis and impairs humoral alloimmunity in murine aortic allografts - Heim, Christian; Eckl, Sebastian; Preidl, Raimund; Ramsperger-Gleixner, Martina; Koch, Nina; Goldmann, Katja; Spriewald, Bernd M.; Weyand, Michael; Ensminger, Stephan M. (European Journal of Cardio-Thoracic Surgery, 2015)
It was previously shown that the combination of clopidogrel and everolimus reduced the development of transplant arteriosclerosis. The aim of this study was to investigate whether delayed onset of treatment, similar to the clinical situation after heart transplantation, inhibits progression of transplant arteriosclerosis.Fully allogeneic C57BL/6 (H2-b) donor aortas were transplanted into CBA.J (H2-k) recipients treated with clopidogrel and everolimus alone or in combination starting on Days 1, 7 or 14. Grafts were analysed by histology and alloantibodies were detected by fluorescence activated cell sorting after transplantation.Delayed platelet inhibition with clopidogrel reduced the development of transplant arteriosclerosis [neointima formation (Day 14): 50 ± 4 vs 84 ± 9% (control)]. The combination of clopidogrel and everolimus almost abolished formation of transplant arteriosclerosis when therapy was started on Day 1 [neointima formation (Day 1): 14 ± 5 vs 84 ± 9% (control)] and also showed a remarkable reduction in both delayed treatment groups [neointima formation (Day 7): 24 ± 7 vs 84 ± 9% (control); neointima formation (Day 14): 28 ± 11 vs 84 ± 9% (control)]. Platelet inhibition alone and in combination with everolimus resulted in reduced alloantibody production.These results demonstrate that delayed treatment with clopidogrel and everolimus-representative of a clinical setting-prevents the progression of transplant arteriosclerosis and impairs humoral immunity in this experimental model.
EVALuna2:16087

Die unterschätzte Rolle von Thrombozyten bei der Herztransplantation. The underestimated role of platelets in heart Transplantation. - Heim, Christian; Eckl, Sebastian; Weyand, Michael; Ensminger, Stephan; et al. (Zeitschrift für Herz-, Thorax- und Gefäßchirurgie, 2010)

Murine cytomegalovirus infection leads to increased levels of transplant arteriosclerosis in a murine aortic allograft model - Heim, Christian; Abele-Ohl, Silke; Eckl, Sebastian; Ramsperger-Gleixner, Martina; Mahmoudian, Shohreh; Weyand, Michael; Stamminger, Thomas; Ensminger, Stephan M. (Transplantation, 2010)
Introduction. Cytomegalovirus infection after heart transplantation is considered as risk factor for the development of transplant arteriosclerosis. Therefore, the aim of this study was to investigate the effect of murine cytomegalovirus (MCMV) as a single risk factor on transplant arteriosclerosis in an experimental aortic allograft model. Methods. Major histocompatibility complex class I-mismatched aortas of C.B10-H2(b)/LilMcdJ donor were transplanted into BALB/c recipients, which were either mock-infected or infected with MCMV (strain Smith) on day 7 and harvested 37 days after transplantation. In one experimental group animals received a daily dose of everolimus to increase the viral load of recipients. Grafts were analyzed by histology, morphometry, and immunofluorescence. Intragraft cytokine mRNA production was analyzed by real-time polymerase chain reaction (PCR), and persistence of cytomegalovirus infection was confirmed by TaqMan PCR. Results. After infection with MCMV, there was significantly more intimal proliferation when compared with uninfected controls (intimal proliferation 83.5%±9.6% [MCMV+] vs. 43.9%±5.1% [MCMV+]), indicating that MCMV plays a role in the development of transplant arteriosclerosis. Even after treatment with everolimus, MCMV infection pronounced significantly more intimal proliferation (intimal proliferation 52.5%±7.3% [MCMV+] vs. 20.2%±1.7% [MCMV+]). Intragraft mRNA expression showed significantly higher production of CD62E, intercellular adhesion molecule-1, and vascular cell adhesion molecule-1 after infection with MCMV. Cellular infiltration revealed significantly more CD4+, CD8+, and dendritic cells. We could also confirm the presence of MCMV for the duration of the experimental protocol by PCR within the spleen, liver, salivary glands, lung, and the aortic transplant. Conclusion. These data suggest that MCMV infection plays an important role in the development of transplant arteriosclerosis. © 2010 by Lippincott Williams & Wilkins.
CRIS-Team Scopus Importer:2024-06-04
Keywords: Adhesion molecules; Dendritic cells; Murine cytomegalovirus; Transplant arteriosclerosis